THE EFFECT OF COMMUNICATION ON EMPLOYEE PERFORMANCE AT THE LAWAWOI COMMUNITY HEALTH CENTER, SIDENRENG RAPPANG REGENCY - Sehrly Agus Yahya; Haeril Haeril; Suriadi Suriadi (Universitas Ichsan Sidenreng Rappang, 2024)
The effect of communication on employee performance at the Lawawoi Community Health Center, Sidenreng Rappang Regency. Communication is felt to be very important in all aspects of life. Pmmunicationis able to increase work harmony in the organization and conversely, if communication isnot effective then coordinaton will be disrupted and result in disruption of the process of achieving instant targets and goals. This research aims to evaluate whether communication has a positive and significant influence on employee performance at the Puskesmas Lawawoi Community Health Center, Sidenreng Rappang Regency. The research method used is quantitative research. The research population consisted of 128 employees at the Puskesmas Lawawoi Community Health Center, Sidenreng Rappang Regency, using a purposive sampling technique with a saturated sampling approach. The results of the analysis show that communication has a significant influence on employee performance, with a calculated t value (8.943) which is greater than the t table (1.797). Therefore, the hypothesis which states that there is an influence of communication on employee performance can be accepted. The coefficient of determination (R Square) value is 38.8%, indicating that 38.8% of employee performance variability can be explained by communication, while the remaining 61.2% is influenced by other factors outside the variables studied